The Declaration of Sydney on human death - Machado, C. (Journal of medical ethics, 2007)
On 5 August 1968, publication of the Harvard Committee’s report on the subject of “irreversible coma” established a standard for diagnosing death on neurological grounds. On the same day, the 22nd World Medical Assembly met in Sydney, Australia, and announced the Declaration of Sydney, a pronouncement on death, which is less often quoted because it was overshadowed by the impact of the Harvard Report. To put those events into present-day perspective, the authors reviewed all papers published on this subject and the World Medical Association web page and documents, and corresponded with Dr A G Romualdez, the son of Dr A Z Romualdez. There was vast neurological expertise among some of the Harvard Committee members, leading to a comprehensible and practical clinical description of the brain death syndrome and the way to diagnose it. This landmark account had a global medical and social impact on the issue of human death, which simultaneously lessened reception of the Declaration of Sydney. Nonetheless, the Declaration of Sydney faced the main conceptual and philosophical issues on human death in a bold and forthright manner. This statement differentiated the meaning of death at the cellular and tissue levels from the death of the person. This was a pioneering view on the discussion of human death, published as early as in 1968, that should be recognised by current and future generations.